1952
DOI: 10.1042/bj0520387
|View full text |Cite
|
Sign up to set email alerts
|

Tracer studies with the B12 vitamins. 2. Biosynthesis of vitamin B12labelled with 60CO and 32P

Abstract: These attempts failed because the livers contained negligible amounts of vitamin B12. We recognized at the time that it would have been preferable to use ruminants, but such animals were not available to us. Subsequent work suggests that we ought to have extracted the faeces rather than the livers of our animals.About the same time we succeeded in preparing very small amounts of radioactive vitamin B12 concentrates by fermentations with Aerobacter aerogenes isolated from hen faeces. More recently we have retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1954
1954
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…We produced eight batches of ). The best specific activity achieved was now 1000 times higher than previously achieved by us and a million times than reported in the pioneering work of Smith et al 1 The specific activities of some batches were still low, obviously related to the difficulty of the organism to thrive in low-phosphorus medium. …”
Section: Preparation Of Labelled Compoundsmentioning
confidence: 47%
See 1 more Smart Citation
“…We produced eight batches of ). The best specific activity achieved was now 1000 times higher than previously achieved by us and a million times than reported in the pioneering work of Smith et al 1 The specific activities of some batches were still low, obviously related to the difficulty of the organism to thrive in low-phosphorus medium. …”
Section: Preparation Of Labelled Compoundsmentioning
confidence: 47%
“…Following the isolation of vitamin B 12 , cobalamin (Cbl), a number of radiolabels were introduced into the molecule, 1 but soon radiocobalt isotopes became almost exclusively used as tracers. Using radiocobalt-labelled Cbl, usually in cyano form (CN-Cbl), a large number of observations have been made regarding the absorption, transport, distribution, excretion, and nutritional requirement of this vitamin.…”
Section: Introductionmentioning
confidence: 99%
“…Early investigators demonstrated that cyanocobalamin could be labeled with cobalt radionuclides (Co-57, -58, -60) (7)(8)(9)(10)(11)(12)(13)(14) and carbon-14 (15). Tritium has also been used to radiolabel cyanocobalamin (16).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to heme and chlorophyll the central atom of vitamin B12 can neither be removed nor exchanged with other metals [1 ]. Studies of the function of the cobalt in the B12-coenzyme have been hindered by the limited availability of the relevant substituted corrinoids.…”
Section: Introductionmentioning
confidence: 99%